LAKE URMIA – ITS PAST AND PRESENT (Proceedings of the YSU C: Geological and Geographical Sciences, 2020)
For the first time, a diagram of Paleo-Urmia was drawn up – a lake that existed in the Late Pliocene-Pleistocene and at a water level of 1570 m had a connection with the Caspian Sea basin in the Pleistocene. Fluctuations in the lake level in the past and up to the 90s of the XX century were mainly associated with a natural factor (tectonics, climate change), and its catastrophic drying out, starting in 1998, is mainly due to the careless use of water resources of the lake’s drainage basin.
Keywords: anthropogenic factor; climate; drought; drying out; Lake Urmia; Palaeolake